Recombinant tissue inhibitor of metelloproteinase-3 from canine mammary tumor induces apoptosis in-vitro - YADAV, PAVAN KUMAR; KUMAR, B V SUNIL; CHANU, K H VICTORIA; YADAV, BRIJESH SINGH; KUMAR, AJAY; KATARIA, MEENA (The Indian Journal of Animal Sciences, 2015)
Tissue inhibitor of metelloproteinases-3 (TIMP-3) is an endogenous inhibitor of matrix metelloproteinases (MMPs). TIMP-3 is tightly bound to the extracellular matrix and it restrains the tumor growth by inhibiting matrix metelloproteinases (MMPs) as well as members of ADAM and ADMTS proteinases families by binding to their active site in a 1:1 stoichiometric ratio. The currently known TIMPs (TIMP-1, 2, 3 and 4) are very well-conserved in humans, other vertebrates, insects, and even in nematode Caenorhabditis elegans. The present work was carried out to produce recombinant canine (Canis lupus familiaris) TIMP-3 protein lacking the signal peptide in E. coli using expression vector pPROEXH-Tc. The TIMP-3 mature peptide encoding gene was successfully cloned and expressed in E. coli and the purified recombinant protein was found to be functionally active and it showed apoptotic activity on MDCK cells.